Effects of p-AlGaN EBL thickness on the performance of InGaN green LEDs with large V-pits. (21st December 2015) - Liu, Xiaohui; Liu, Junlin; Mao, Qinghua; Wu, Xiaoming; Zhang, Jianli; Wang, Guangxu; Quan, Zhijue; Mo, Chunlan; Jiang, Fengyi
Abstract: The effects of the p-AlGaN electron blocking layer (EBL) thickness on the performance of InGaN/GaN multiple quantum wells (MQWs) green light emitting diodes (LEDs) was investigated. It was observed that increasing the thickness of the p-AlGaN EBL could reduce the leakage current and improve the efficiency of green LEDs with large V-pits. It is proposed that increasing the EBL thickness leads to a thicker p-AlGaN on the sidewalls of V-pits, which provides a thicker energy barrier and consequently screens dislocations more effectively. The leakage current (at −5 V) of LEDs with a 40 nm EBL is about an order of magnitude lower than that of LEDs with a 20 nm EBL. With the increase in EBL thickness, at low current densities, the external quantum efficiency (EQE) firstly decreases and then increases afterwards, which could be attributed to the competition between the enhancement of the radiative recombination rate and the reduction of the hole injection efficiency. At operating current density, there is a positive correlation between EQE and the thickness of the EBL. This is attributed to the improved electron confinement in the active region by preventing electrons overflowing to the p-type layer. Meanwhile, the efficiency droop is obviously suppressed when the thickness of the EBL increases from 20 nm to 40 nm. However, further increasing the thickness of the EBL may deteriorate the EQE and efficiency droop. Packaged green LED chips with an optimized EBL emit 260 mW (dominant wavelength: 520 nm) at 350 mA (35 A cm −2 ), and the EQE reaches 31.2%.